Estimation of Metabolic Faecal Nitrogen from Nitrogen Balance Experiments in Buffaloes - Bhargava, V.N.; Singh, V.P.; Singh, P.K. (Indian Journal of Animal Nutrition, 2018)
Data on daily nitrogen intake (X) and faecal nitrogen (Y) excretion both expressed as g/100 g of DM consumed were collected from long and short range 4 experiments covering 9 nitrogen balance trials conducted at varied intervals on 3 groups each of 8 non-producing adult male buffaloes. In each experiment, the 3 groups were offered 3 levels of digestible crude protein (DCP) which covered 0.60, 0.50, 0.45, 0.40, 0.35, 0.30 and 0.25 kg DCP/100 kg BW/d intakes through rapeseed cake and wheat straw during these 4 experiments. The data comprising 27 pairs of group – means pertaining to X and Y revealed a close positive correlation (r = 0.628; t significant at P<0.01) and was described by a regression equation (Y= 0.34018 + 0.16661 X) which at zero nitrogen intake (X) gave a value of 0.3401 g/100 g of DM consumed for metabolic faecal nitrogen (MFN). It was quite identical with the one determined by actual experimentation.